Proteome of larval metamorphosis induced by epinephrine in the Fujian oyster Crassostrea angulata - Guilan Di; Xiaohuo Xiao; Ming Him Tong; Xinhua Chen; Li Li; Miaoqin Huang; Long Zhou; Caihuan Ke (BMC Genomics, 2020)
Abstract Background The Fujian oyster Crassostrea angulata is an economically important species that has typical settlement and metamorphosis stages. The development of the oyster involves complex morphological and physiological changes, the molecular mechanisms of which are as yet unclear. Results In this study, changes in proteins were investigated during larval settlement and metamorphosis of Crassostrea angulata using epinephrine induction. Protein abundance and identity were characterized using label-free quantitative proteomics, tandem mass spectrometry (MS/ MS), and Mascot methods. The results showed that more than 50% (764 out of 1471) of the quantified proteins were characterized as differentially expressed. Notably, more than two-thirds of the differentially expressed proteins were down-regulated in epinephrine-induced larvae. The results showed that “metabolic process” was closely related to the development of settlement and metamorphosis; 5 × 10− 4 M epinephrine induced direct metamorphosis of larvae and was non-toxic. Calmodulin and MAPK pathways were involved in the regulation of settlement of the oyster. Expression levels of immune-related proteins increased during metamorphosis. Hepatic lectin-like proteins, cadherins, calmodulin, calreticulin, and cytoskeletal proteins were involved in metamorphosis. The nervous system may be remodeled in larval metamorphosis induced by epinephrine. Expression levels of proteins that were enriched in the epinephrine signaling pathway may reflect the developmental stage of the larvae, that may reflect whether or not larvae were directly involved in metamorphosis when the larvae were treated with epinephrine. Conclusion The study provides insight into proteins that function in energy metabolism, immune responses, settlement and metamorphosis, and shell formation in C. angulata. The results contribute valuable information for further research on larval settlement and metamorphosis. Graphical abstract